DESA WISATA EKANG: POTENSI DESA WISATA BERDASARKAN KOMPONEN PARIWISATA 6A - Dian Febrianti; Siti Fatimah (Puteri Hijau : Jurnal Pendidikan Sejarah, 2024)
This research discusses the potential of the Ekang Tourism Village in Ekang Anculai Village using the 6A tourism components, namely, Attractions, Accessibility, Amenities, Available Packages, Activities, Ancillary Services. The aim of this research is to find out what natural and artificial attractions or special interests the Ekang Tourism Village has which are the potential of the Ekang Tourism Village. This research uses a historical research method with four steps, namely, (1) Heuristics (collecting sources), (2) Criticism of both internal and external sources, (3) Interpretation, (4) Historiography, namely compiling facts and their meaning. chronologically. /diachronic in written form. The results of this research show that there are 6A tourism components in the tourism potential of Ekang Tourism Village, namely attractions which include natural and artificial attractions or special interests. Adequate Accessibility for cars and motorbikes. The Amenities at Ekang Tourism Village include accommodation, restaurants, SPA, prayer rooms and meeting rooms. Available Packages that have been planned by the management of Ekang Tourism Village. Activities include exploring the village, horse riding, gardening and others. There are Ancillary Services including security, tour guides, TIC, telecommunications networks and adequate health.